Dynamic Chiro‐Optics of Bio‐Inorganic Nanomaterials via Seamless Co‐Assembly of Semiconducting Nanorods and Polysaccharide Nanocrystals. (28th July 2021) - Kang, Saewon; Biesold, Gill M.; Lee, Hansol; Bukharina, Daria; Lin, Zhiqun; Tsukruk, Vladimir V.
Abstract: This study demonstrates a novel chiral organization of multi‐materials from semiconducting quantum nanorods (QNRs) co‐assembled into chiral nematic polysaccharide (cellulose) nanocrystals for active manipulation of chiro‐optical light emission properties in elastomeric materials. Highly emissive anisotropic QNRs with dimensions and surface chemistry commensurate with those of biological nanocrystals facilitate seamless co‐assembly into an integrated chiral nematic organization due to preferable enthalpic interactions and pairing processes. The resulting freestanding highly emissive bio‐inorganic elastomeric materials exhibit vivid iridescence and emission with a strong optical activity that manifests itself in active and tunable chiral photoluminescence with unusually large asymmetry. Intriguingly, large‐strain reversible mechanical deformation of physically crosslinked elastomers endows fully reversible alternation of helical structural configuration and corresponding linearly and circularly polarized photoluminescence. This study provides a platform to render dynamic optical functionality with reconfigurable light propagation/emission in bio‐inorganic elastomers for futuristic applications in chiral lasing, biosensing, optical gauges, and holographic display. Abstract : Highly emissive quantum nanorods bearing well‐defined dimensions and surface chemistry commensurate with cellulose nanocrystals enable the construction of bio‐inorganic chiral nematic‐like elastomers via seamless co‐assembly, resulting in strongly polarized light emission with large asymmetry. Reversible mechanical deformation of these composites triggers structural reconfiguration to regulate linearly and circularly polarized photoluminescence.